Preliminary Needs Assessment and CSR–Zakat Strategy during the Exploration Phase of the Pongkeru Nickel Project for Sustainable and Social Legitimacy - Muh Ridwansyah; Ameen Talib (Journal of Islamic Economic Studies, 2026)
The mining industry, particularly the nickel sector contributes significantly to Indonesia’s economic development but also generates social and environmental challenges. Corporate social responsibility (CSR) is widely used to address these impacts, yet its effectiveness remains limited when implemented in a reactive manner. This study aims to map the socio-economic needs of communities in the Pongkeru mining area and to formulate a strategic CSR–zakat framework during the exploration phase as a foundation for long-term sustainability and social legitimacy. A descriptive qualitative approach was employed using field observations, semi-structured interviews, focus group discussions, and document analysis. Data were analyzed through thematic analysis and SWOT frameworks to identify structural vulnerabilities and develop a strategic CSR–zakat roadmap. The findings reveal that local communities face structural challenges, including dependence on agriculture and micro-enterprises, limited access to skills development, and exposure to environmental risks. Early-stage CSR interventions grounded in systematic needs assessment and integrated with zakat significantly enhance social, economic, and environmental sustainability. The study confirms that CSR designed during the exploration phase offers a strategic opportunity to prevent social conflict, strengthen community trust, and build long-term partnerships, while conventional CSR alone remains insufficient. The study implies that a hybrid CSR–zakat model aligned with Maqasid al-Shariah provides a comprehensive and accountable governance framework combining workforce development, MSME empowerment, social protection, and environmental stewardship. This framework contributes theoretically to mining CSR literature and offers practical guidance for designing inclusive, preventive, and sustainable CSR strategie.